Antibacterial activity of endolysin LysP70 from Listeria monocytogenes phage - Zhang, Kunzhong; Zhao, Xuehui; Cao, Qing; Chong, Qian; Fan, Ziqiu; Zhi, Ji; He, Jiabing; Wang, Jiayu; Wang, Zhonglong; Cheng, Mingxia; Xiao, Min; Wang, Zijian; et al. (Frontiers in Microbiology, 2025)
Endolysins, which are potential antimicrobial agents, can directly lyse gram-positive bacteria from the exterior. In this study, the endolysin gene derived from Listeria phage P70 was cloned, expressed, and purified, and designated LysP70. The antibacterial efficacy of LysP70 was comprehensively assessed through plate counting and electron microscopy. The findings indicate that LysP70 is composed of 315 amino acids and has a molecular weight of 34.2 kDa, structural stability, and peptidase activity. Successfully expressed and purified LysP70 demonstrated lytic activity against L. monocytogenes, but not against Staphylococcus or Salmonella. LysP70 displayed stable enzymatic activity across a range of pH levels, temperatures, and metal ion concentrations. Furthermore, LysP70 significantly inhibited L. monocytogenes biofilm formation and scavenged existing biofilms, while affecting the transcriptional levels of genes associated with biofilm formation. In terms of food applications, LysP70 was effective in reducing the L. monocytogenes count in milk by 1.9 Log10 CFU/mL. This study offers a novel strategy for the prevention and control of L. monocytogenes infection, and establishes a theoretical basis for the development of endolysin antimicrobial agents.